Elements Driving Profit Increase in The Primary Consumer Industry Sector - Rini Tri Hastuti; Anggraeni Pratama Indrianto; Velinda Alvita (Fundamental and Applied Management Journal, 2026)
For investors, understanding financial variables such as debt ratio, total asset turnover, and net profit margin can assist in investment decision-making. Investors can assess potential profit growth from published financial statements and more accurately estimate investment returns. This research serves to provide a theoretical contribution to enrich the literature on corporate finance and profit growth. Several previous studies have been conducted to examine these variables, but there are gaps in the results from one study to another. Therefore, this study attempts to re-examine the gaps found in several studies. This study aims to re-examine and obtain evidence in the form of the influence of debt ratio, total asset turnover, and net profit margin on profit growth. Companies listed on the IDX during the 2021-2023 period. Using a purposive sampling method and using data containing 118, equivalent to 53 companies. The technique in this study uses multiple regression analysis assisted by the IBM SPSS Statistics program version 30 and Microsoft Excel Workbook. The results of this study indicate that the debt ratio and total asset turnover both have no effect on profit growth and exhibit a negative relationship. Meanwhile, in this study, the net profit margin has a negative effect on profit growth. The implication of this study is that using a good debt ratio, maximizing asset utilization, and calculating the net profit margin correctly can increase profit growth in a company, thus providing a positive signal to potential investors.